2014
DOI: 10.1007/s00122-014-2338-3
|View full text |Cite
|
Sign up to set email alerts
|

Marker-assisted introgression of a QTL region to improve rust resistance in three elite and popular varieties of peanut (Arachis hypogaea L.)

Abstract: Key messageSuccessful introgression of a major QTL for rust resistance, through marker-assisted backcrossing, in three popular Indian peanut cultivars generated several promising introgression lines with enhanced rust resistance and higher yield.AbstractLeaf rust, caused by Puccinia arachidis Speg, is one of the major devastating diseases in peanut (Arachis hypogaea L.). One QTL region on linkage group AhXV explaining upto 82.62 % phenotypic variation for rust resistance was validated and introgressed from cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
149
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(156 citation statements)
references
References 31 publications
2
149
0
5
Order By: Relevance
“…Nonetheless, selected major QTLs identified in this study can be further confirmed for their use in molecular breeding to enhance resistance to leafspot disease, as it was performed previously for other peanut diseases, such as root-knot nematode and rust resistance (Burow et al 2014;Varshney et al 2014). Transferring one or more of these QTLs to different genetic backgrounds and developing near-isogenic lines (NILs) will help validate the usefulness of these loci for future breeding programs.…”
Section: Qtls For Leafspot Resistancesupporting
confidence: 58%
“…Nonetheless, selected major QTLs identified in this study can be further confirmed for their use in molecular breeding to enhance resistance to leafspot disease, as it was performed previously for other peanut diseases, such as root-knot nematode and rust resistance (Burow et al 2014;Varshney et al 2014). Transferring one or more of these QTLs to different genetic backgrounds and developing near-isogenic lines (NILs) will help validate the usefulness of these loci for future breeding programs.…”
Section: Qtls For Leafspot Resistancesupporting
confidence: 58%
“…Marker assisted selection or introgression for major QTLs in peanut has been performed for rust resistance in peanut (Varshney et al 2014). Reports on this variation in recombinant inbred population and identification of genomic regions controlling such variation is valuable for marker assisted selection of peanut with enhanced amount of these bioactive compounds in seeds.…”
Section: Qtls For Tpc Tfc and Dpphrsa In Peanutmentioning
confidence: 99%
“…However, over the last decade, significant developments have been made in the use of various molecular approaches for biotic stress management in peanuts, and new efforts such as functional genomics are likely to play key roles in the future Varshney et al, 2014;Gajjar et al, 2014). Recently, Kanyika et al (2015) has identified 376 polymorphic SSR markers in 16 African groundnut cultivars with a wide range of disease resistance.…”
Section: Introductionmentioning
confidence: 98%
“…Marker-assisted selection (MAS) offers great promise for improving the efficiency of conventional plant breeding , including the potential to pyramid resistance genes in peanuts (Mishra et al, 2009;Varshney et al, 2014;Pandey et al, 2012). For any molecular breeding program, assessment of genetic diversity and development of genetic linkage maps are two very important steps (Dwivedi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%